2019
DOI: 10.1186/s40798-019-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

The Training and Development of Elite Sprint Performance: an Integration of Scientific and Best Practice Literature

Abstract: Despite a voluminous body of research devoted to sprint training, our understanding of the training process leading to a world-class sprint performance is limited. The objective of this review is to integrate scientific and best practice literature regarding the training and development of elite sprint performance. Sprint performance is heavily dependent upon genetic traits, and the annual within-athlete performance differences are lower than the typical variation, the smallest worthwhile change, and the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
209
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(262 citation statements)
references
References 145 publications
3
209
1
7
Order By: Relevance
“…In sprinters, the expected lack of significant changes in max between consecutive training phases (despite desired changes in body composition, i.e., fat mass reduction) results from their specific training and performance requirements. Sprint is an all-out high-intensity exercise and the distance covered during competition (including acceleration, achieving maximal velocity, and deceleration) lasts for up to several seconds [ 26 ]. It is recommended that elite sprinters should primarily focus on increasing their relative muscle power production using ballistic exercises to maximize speed performance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sprinters, the expected lack of significant changes in max between consecutive training phases (despite desired changes in body composition, i.e., fat mass reduction) results from their specific training and performance requirements. Sprint is an all-out high-intensity exercise and the distance covered during competition (including acceleration, achieving maximal velocity, and deceleration) lasts for up to several seconds [ 26 ]. It is recommended that elite sprinters should primarily focus on increasing their relative muscle power production using ballistic exercises to maximize speed performance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present findings showed that integrating cognitive behavioral-based therapy into intervention resulted in significant improvement in functional ability when performing activities of daily living. Nevertheless, the improvement in functional ability in sports was not found to be significant, presumably because sporting activities require a certain level of training and practice [45][46][47].…”
Section: Discussionmentioning
confidence: 94%
“…The stage of initial sports specialization (12-14 years) should be considered as the most important and responsible in the course of longterm sports preparation of young runners on short distances (Haugen et al, 2019). The optimum period to develop the elementary forms of speed for boys is the age of 7-9 and 13-16 years (Way et al, 2016).…”
Section: Introductionmentioning
confidence: 99%